A missed opportunity for public health: How impact assessment shaped EU rules on the marketing of unhealthy commodities to children - Kathrin Lauber; Eleanor Brooks (Elsevier, 2024)
Background: The 2015-2018 revision of the European Union's Audiovisual Media Services Directive, which governs the marketing of alcohol and unhealthy food to minors, failed to align with international best practice. Previous research has explained this 'missed opportunity' with reference to deficient political will, difficulties advocating for health, and industry pressure. We explore another explanation: the role of the impact assessment (IA) process in shaping decision-making. Methods: We first conducted an in-depth comparison of three versions of the IA report, employing qualitative content and framing analyses to establish what changed in the substantive content, framing, and evidence cited. Second, we used process-tracing, a qualitative method drawing on multiple data sources, to explore causal mechanisms, to assess why these changes occurred. Data sources include policy documents published proactively and obtained through access-to-document requests. Findings: Previously unpublished versions of the IA report show that stronger rules on advertising were preferred early in the policy process but later abandoned, and that concern for 'balancing' consumer protection and competitiveness shifted to focus on the latter. Following review by the Regulatory Scrutiny Board, a revised IA report narrowed the policy options, removing a requirement for member states to prevent childrens' exposure to alcohol advertising. Consequently, decision-makers were provided with an IA that did not offer adequate information on available measures to protect children. Interpretation: Changes made during the IA process, which determines the policy options presented to decision-makers, side-lined health concerns. We argue that engaging with the institutional structures which shape decision-making is crucial for those working to further public health.